Design and Analysis of Rectangular Microstrip Patch Antenna - Vidhya, Dr.K. (International Journal of Psychosocial Rehabilitation, 2020)
In this paper rectangular microstrip patch antenna is designed and analysed for several wireless and broadband communication applications. This rectangular microstrip patch antenna has ground plane on one side and on the other side of its substrate having radiating patch which will radiate the power. The microstrip patch has dielectric material such as gold or copper with any desired shape. The rectangular patch is act like a radiator. Several advantages of this type of broadband antenna like it is a planar, flexible construction, compact size and easily fabricated thus it is useful for several practical applications. This rectangular microstrip patch antenna is designed, constructed and analysed for several wireless communication applications that operate at 5.2 GHz for different environment. It also has a broad angle of beam in its radiation pattern. Several results are obtained in rectangular microstrip patch antenna that is used as reference antenna in computer and which antenna is used for wireless fidelity. Simulated results are taken using HFSS software tool in this work.